Protocol to calculate the climate effects of the global aviation industry using the Aviation-FAIR model - Qiang Cui; Ying Zhou (STAR Protocols)
Summary: The rapid growth of the aviation industry has significantly impacted global climate change. We present a protocol to assess the climate effects of global aviation emissions. We describe steps for calculating annual emissions; greenhouse gas concentrations; effective radiative forcing from gases, contrails, and aerosols; and temperature variations under different scenarios. We also outline how to analyze the potential impacts of mitigation strategies.For complete details on the use and execution of this protocol, please refer to Cui et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.